The Prebiotic Effects of Oats on Blood Lipids, Gut Microbiota, and Short-Chain Fatty Acids in Mildly Hypercholesterolemic Subjects Compared With Rice: A Randomized, Controlled Trial - Xu, Dengfeng; Feng, Meiyuan; Chu, YiFang; Wang, Shaokang; Shete, Varsha; Tuohy, Kieran M.; Liu, Feng; Zhou, Xirui; Kamil, Alison; Pan, Da; Liu, Hechun; Yang, Xian; et al. (Frontiers in immunology, 2021)
Phytochemicals derived from oats are reported to possess a beneficial effect on modulating dyslipidemia, specifically on lowering total and LDL cholesterol. However, deeper insights into its mechanism remain unclear. In this randomized controlled study, we assigned 210 mildly hypercholesterolemic subjects from three study centers across China (Beijing, Nanjing, and Shanghai) to consume 80 g of oats or rice daily for 45 days. Plasma lipid profiles, short chain fatty acids (SCFAs), and fecal microbiota were measured. The results showed that total cholesterol (TC) and non-high-density lipoprotein cholesterol (non-HDL-C) decreased significantly with both oats and rice intake after 30 and 45 days. The reduction in TC and non-HDL-C was greater in the participants consuming oats compared with rice at day 45 ( p = 0.011 and 0.049, respectively). Oat consumption significantly increased the abundance of Akkermansia muciniphila and Roseburia , and the relative abundance of Dialister , Butyrivibrio , and Paraprevotella , and decreased unclassified f-Sutterellaceae. In the oat group, Bifidobacterium abundance was negatively correlated with LDL-C ( p = 0.01, r = −0.31) and, TC and LDL-C were negatively correlated to Faecalibacterium prausnitzii ( p = 0.02, r = −0.29; p = 0.03, r = −0.27, respectively). Enterobacteriaceae , Roseburia , and Faecalibacterium prausnitzii were positively correlated with plasma butyric acid and valeric acid concentrations and negatively correlated to isobutyric acid. HDL-C was negatively correlated with valeric acid ( p = 0.02, r = −0.25) and total triglyceride (TG) was positively correlated to isovaleric acid ( p = 0.03, r = 0.23). Taken together, oats consumption significantly reduced TC and LDL-C, and also mediated a prebiotic effect on gut microbiome. Akkermansia muciniphila , Roseburia , Bifidobacterium , and Faecalibacterium prausnitzii , and plasma SCFA correlated with oat-induced changes in plasma lipids, suggesting prebiotic activity of oats to modulate gut microbiome could contribute towards its cholesterol-lowering effect.